PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN DI PT.FCC INDONESIA KARAWANG - Pauji, Ipan; Solehudin, Solehudin (Universitas Gorontalo, 2023)
The author tries to do an analysis of PT. FCC Indonesia is a company engaged in the manufacturing sector, which continues to strive to maximize internal performance, which means that the company must understand the workload of each employee at work which will improve employee performance. This study aims to determine and analyze the effect of workload on employee performance. The method used in this study is to use path analysis using a quantitative approach. The research aid is SPSS software version 26. The variables used in this study are workload (X) and performance (Y). The sample used in this research is PT. FCC Indonesia as many as 90. The results of this study indicate that workload has a significant influence on good performance.